Zoë Wicomb’s Playing in the Light : Home, Homesickness, and Race as Place - Yates, Sarah (WritingThreeSixty, 2018)
Marion’s journey in Playing in the Light can be read as a metaphor for South Africa in general. This is evident in three aspects of the novel: firstly, the anxiety surrounding post-apartheid racial identity and the meaninglessness of categories once ―pot-bellied with meaning‖, secondly the Truth and Reconciliation Commission (TRC) as a trigger for this anxiety, and thirdly the idea of the repressed resurfacing to haunt the present (Wicomb, Playing in the Light 106). Wicomb’s protagonist goes on a journey of discovery after seeing a picture of a woman who resembles her childhood domestic worker in a newspaper. Her parents’ past comes back to colour her current identity and understanding of her past and that of her country. This resurgence of the repressed mirrors not only the trauma of Marion’s past, but also that of South Africa in general during the transition f rom apartheid to democracy, and specifically that of coloured people. Through an exploration of the resurgence of the repressed and race as place, Wicomb navigates and deconstructs whiteness and race in general. By reading the novel as diasporic in terms of the way Wicomb uses motifs of home, belonging, homesickness and un-belonging as a spatial metaphor for race, this paper argues that Playing in the Light has implications for the ways in which we read race, particularly in a postcolonial context.